2008
DOI: 10.1089/hum.2008.079
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sorting of Human Parathyroid Hormone After Transduction of Mouse and Rat Salivary Glands

Abstract: Gene transfer to salivary glands leads to abundant secretion of transgenic protein into either saliva or the bloodstream. This indicates significant clinical potential, depending on the route of sorting. The aim of this study was to probe the sorting characteristics of human parathyroid hormone (hPTH) in two animal models for salivary gland gene transfer. PTH is a key hormone regulating calcium levels in the blood. A recombinant serotype 5 adenoviral vector carrying the hPTH cDNA was administered to the subman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Over the last ~15 years we have studied the concept of employing salivary glands as a surrogate endocrine organ using several model human proteins, including α-1-antitrypsin (α1AT), erythropoietin (Epo), growth hormone (GH) and parathyroid hormone (PTH) [4,7,12, 23,24]. While results with α1AT and GH have been relatively straightforward, studies with Epo and PTH were not predictable, with differences in their secretory behavior occurring between certain species and gland types [e.g., 12,2327].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last ~15 years we have studied the concept of employing salivary glands as a surrogate endocrine organ using several model human proteins, including α-1-antitrypsin (α1AT), erythropoietin (Epo), growth hormone (GH) and parathyroid hormone (PTH) [4,7,12, 23,24]. While results with α1AT and GH have been relatively straightforward, studies with Epo and PTH were not predictable, with differences in their secretory behavior occurring between certain species and gland types [e.g., 12,2327].…”
Section: Introductionmentioning
confidence: 99%
“…IVM relies on the use of fluorescently tagged proteins that can be either expressed in adult animals or introduced into mouse germ lines. In adult animals, genes can be delivered to selected organs using different approaches: One example being the administration of transgenes to the rat submandibular salivary glands through the salivary duct (Wharton’s duct) by using either non-viral or viral methods [13, 14]. Focusing specifically on non-viral delivery, we express fluorescently-tagged Lifeact in the acinar cells by mixing plasmid DNA with polyethyleneimine (PEI), a molecule extensively used for in vivo siRNA delivery [15].…”
Section: Methodsmentioning
confidence: 99%
“…SG cells can also secrete protein into the circulation via their basolateral membranes, which is thought to occur via the constitutive secretory pathway (CSP) [6], [7]. Although the route of secretion for transgenic proteins is not entirely predictable in vivo , we have shown that vectors targeted to the SG can lead to secretion of therapeutic levels of many transgenic proteins, such as growth hormone [8], parathyroid hormone [9], erythropoietin [10] and glucagon-like peptide-1 (GLP-1) [2] via the CSP as a potential treatment for endocrine disorders.…”
Section: Introductionmentioning
confidence: 99%